The Relationship between Liberalisation in the Logistics Sector and Trade Facilitation - D. De Sousa; C. Findlay (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
This study demonstrates that the improvement of the performance of logistics services through domestic liberalisation may generate a virtuour cycle, whereby international trade is increased and the this, in turn, may increase the deman for logistics services.
Keywords: F1; 330; Liberalisation; Logistics Sector; Trade Facilitation